The Impact of Law Harmonization Tax Regulations Implementation on the Compliance of Micro, Small and Medium Enterprises Taxpayers - Kusumaningrum, Nurcahyaning Dwi; Wicaksono, Galih; Asmandani, Venantya; Puspita, Yeni (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Purpose: The purpose of this study is to examine the impact of the Harmonization of Tax Regulations Law (HPP Law), enforced since October 29, 2021, on the compliance of micro, small, and medium enterprise (MSME) taxpayers. Specifically, the study aims to explore how the implementation of the HPP Law influences MSME taxpayer compliance through taxpayer awareness. Methodology: This research employs quantitative approach, combining both quantitative and qualitative analyses. The research process includes internal team discussions, acquiring research permits, conducting field surveys in the Jember, Bondowoso, Banyuwangi, and Situbondo regions. Findings: Preliminary results suggest that the enforcement of the HPP Law has a direct impact on MSME taxpayer compliance, mediated by their taxpayer awareness. The study identifies common concerns among MSME operators regarding rising prices of production and supporting materials, increased costs, and pressure to raise employee wages due to surges in the prices of essential goods. Implication: The findings highlight the challenges MSMEs face under the HPP Law, particularly concerning compliance and financial management. Policymakers may need to consider these financial pressures when designing regulations or support systems for MSMEs to enhance their ability to comply with tax regulations without compromising business sustainability. Originality: This study provides a unique combination of quantitative insights into the impact of the HPP Law on MSME taxpayer compliance in East Java, Indonesia. It also offers valuable quantitative data from MSME business actors, which enriches the understanding of how Taxpayer awareness mediate the relationship between tax regulation enforcement and compliance.